Implementasi Pengembangan Ekowisata Magrove di Wonorejo Dengan Partisipasi Masyarakat Desa Wonorejo Surabaya - Imam Dakhwan; Dida Rahmadanik; Adi Soesiantoro (Jurnal Hukum dan Sosial Politik, 2025)
The development of mangrove ecotourism in the Wonorejo area of Surabaya represents an effort to preserve the environment while simultaneously empowering the local economy. This study aims to analyze the implementation of mangrove ecotourism development through active participation of the Wonorejo village community. A qualitative research approach was employed, utilizing data collection techniques such as observation, in-depth interviews, and documentation. The results indicate that community participation is evident in various aspects, including ecotourism management, tourism service provision, and environmental education. However, the development process still faces several challenges, such as limited infrastructure access, funding constraints, and the need to enhance human resource capacity. Therefore, collaboration between the government, local communities, and private stakeholders is essential to establish a sustainable ecotourism ecosystem that provides balanced economic, social, and ecological benefits.